Metodologias colaborativas: narrativas de professores e professoras para o ensino e aprendizagem nas Ci?ncias Cont?beis - Silva, Marival Rodrigues (2024)
The general aim of this study is to understand specifically how collaborative methodologies contribute to the development of teaching and learning processes in Accounting. The research's guiding question is: how do collaborative methodologies contribute to the development of teaching and learning processes in Accounting? The methodological path used highlights the narratives as both a method and a research device. The research participants were seven teachers from a state university in Bahia. The narratives were analyzed using comprehensive-interpretive analysis. As the main results, the research shows that through the narratives it was possible to understand concepts such as experience and affectivity, map collaborative teaching and learning methodologies such as PBL, Business Games, Co-creation and the emergence of role-playing as a teaching methodology for personal finance.